2018
DOI: 10.1038/s41467-017-02645-3
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus infection induces host inflammatory responses by facilitating NLRP3 inflammasome assembly and interleukin-1β secretion

Abstract: Zika virus (ZIKV) infection is a public health emergency and host innate immunity is essential for the control of virus infection. The NLRP3 inflammasome plays a key role in host innate immune responses by activating caspase-1 to facilitate interleukin-1β (IL-1β) secretion. Here we report that ZIKV stimulates IL-1β secretion in infected patients, human PBMCs and macrophages, mice, and mice BMDCs. The knockdown of NLRP3 in cells and knockout of NLRP3 in mice inhibit ZIKV-mediated IL-1β secretion, indicating an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
185
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 179 publications
(194 citation statements)
references
References 54 publications
8
185
0
1
Order By: Relevance
“…The role of CUL1 in regulation of the NLRP3 inflammasome was determined in a reconstructed NLRP3 inflammasome system, in which HEK293T cells were cotransfected with plasmids encoding NLRP3 inflammasome components (NLRP3, ASC, and pro–Casp‐1) and the substrate pro‐IL‐1β (25, 26). IL‐1β secretion, IL‐1β (p17) cleavage, and Casp–1 (p20) maturation were detected ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of CUL1 in regulation of the NLRP3 inflammasome was determined in a reconstructed NLRP3 inflammasome system, in which HEK293T cells were cotransfected with plasmids encoding NLRP3 inflammasome components (NLRP3, ASC, and pro–Casp‐1) and the substrate pro‐IL‐1β (25, 26). IL‐1β secretion, IL‐1β (p17) cleavage, and Casp–1 (p20) maturation were detected ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As previously described (25), the cell lysates were mixed with SDS‐loading buffer for Western blot analyses using indicating antibodies. The pellets were washed with PBS 3 times and were cross‐linked using fresh DSS (2 mM; MilliporeSigma) at 37°C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Picornavirus has come up with a more dramatic strategy to trigger MDA5 and RIG‐I cleavage and degradation by using host caspases (Barral et al , ). Accumulating evidence from other groups revealed that inflammasome activation is necessary during ZIKV infection (Khaiboullina et al , ; Wang et al , ). Our in vivo experiments also suggest that NLRP3 inflammasome deficiency protects mice from ZIKV infection.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 In this system, HEK293T cells were co-transfected with plasmids encoding the NLRP3 inflammasome components (NLRP3, ASC, and pro-Casp1) and the substrate (pro-IL-1β). 39,40 In this system, HEK293T cells were co-transfected with plasmids encoding the NLRP3 inflammasome components (NLRP3, ASC, and pro-Casp1) and the substrate (pro-IL-1β).…”
Section: Sumo1 Sumoylates Nlrp3 To Promote the Inflammasome Activationmentioning
confidence: 99%